Serum glucose, albumin and total protein levels in camels infected with Trypanosoma evansi in Nyala area - A., Maki; H.S. , Abdalla; M, Mustafa (Journal of Veterinary Medicine and Animal Production, 2021)
Trypanosomosis caused by Trypanosoma evansi constitutes serious and economically important infections in camels in Sudan and elsewhere. The parasite is transmitted by biting flies such as Tabanus and Stomoxys spp.